Venetoclax in combination with cytarabine with or without idarubicin in children with relapsed or refractory acute myeloid leukaemia: a phase 1, dose-escalation study. Issue 4 (April 2020) - Karol, Seth E; Alexander, Thomas B; Budhraja, Amit; Pounds, Stanley B; Canavera, Kristin; Wang, Lei; Wolf, Joshua; Klco, Jeffery M; Mead, Paul E; Das Gupta, Soumyasri; Kim, Su Y; Salem, Ahmed Hamed; et al.
Summary: Background: Outcomes for children with relapsed or refractory acute myeloid leukaemia remain poor. The BCL-2 inhibitor, venetoclax, has shown promising activity in combination with hypomethylating agents and low-dose cytarabine in older adults for whom chemotherapy is not suitable with newly diagnosed acute myeloid leukaemia. We aimed to determine the safety and explore the activity of venetoclax in combination with standard and high-dose chemotherapy in paediatric patients with relapsed or refractory acute myeloid leukaemia. Methods: We did a phase 1, dose-escalation study at three research hospitals in the USA. Eligible patients were aged 2–22 years with relapsed or refractory acute myeloid leukaemia or acute leukaemia of ambiguous lineage with adequate organ function and performance status. During dose escalation, participants received venetoclax orally once per day in continuous 28-day cycles at either 240 mg/m 2 or 360 mg/m 2, in combination with cytarabine received intravenously every 12 h at either 100 mg/m 2 for 20 doses or 1000 mg/m 2 for eight doses, with or without intravenous idarubicin (12 mg/m 2 ) as a single dose, using a rolling-6 accrual strategy. The primary endpoint was the recommended phase 2 dose of venetoclax plus chemotherapy and the secondary endpoint was the proportion of patients treated at the recommended phase 2 dose who achieved complete remission or complete remission with incomplete haematological recovery. Analyses were done on patients who received combination therapy. The study is registered with ClinicalTrials.gov (NCT03194932 ) and is now enrolling to address secondary and exploratory objectives. Findings: Between July 1, 2017, and July 2, 2019, 38 patients were enrolled (aged 3–22 years; median 10 [IQR 7–13]), 36 of whom received combination therapy with dose escalation, with a median follow-up of 7·1 months (IQR 5·1–11·2). The recommended phase 2 dose of venetoclax was found to be 360 mg/m 2 (maximum 600 mg) combined with cytarabine (1000 mg/m 2 per dose for eight doses), with or without idarubicin (12 mg/m 2 as a single dose). Overall responses were observed in 24 (69%) of the 35 patients who were evaluable after cycle 1. Among the 20 patients treated at the recommended phase 2 dose, 14 (70%, 95% CI 46–88) showed complete response with or without complete haematological recovery, and two (10%) showed partial response. The most common grade 3–4 adverse events were febrile neutropenia (22 [66%]), bloodstream infections (six [16%]), and invasive fungal infections (six [16%]). Treatment-related death occurred in one patient due to colitis and sepsis. Interpretation: The safety and activity of venetoclax plus chemotherapy in paediatric patients with heavily relapsed and refractory acute myeloid leukaemia suggests that this combination should be tested in newly diagnosed paediatric patients with high-risk acute myeloid leukaemia. Funding: US National Institutes of Health, American Lebanese Syrian Associated Charities, AbbVie, and Gateway for Cancer Research.